Bala Ghora - Wira yasa, I Made Wira yasa; I Gede Oka Surya Negara; Made Ayu Desiari (Jurnal IGEL : Journal Of Dance, 2025)
Bala Ghora The Bala Ghora dance is a new dance work inspired by Balinese cultural forms which cannot be separated from the traditional and religious activities of the Batulantang Traditional Village community. This dance has a religious function related to the majabajero ceremony at Kayangan Jagat Kancing Gumi Temple. As a work of art, the creation of the Bala Ghora Dance aims to fulfill the graduation requirements for undergraduate students at ISI Denpasar, Dance Study Program in 2024, as well as contributing to the development of the essence of Baris dance as a form of cultural heritage through the creation of creative dances that are modified according to creativity and imagination. The process of creating this dance uses the method of I Wayan Dibia in his book Panca Sthiti Ngawi Sani which includes five stages, namely; the inspiration stage (ngawirasa), the exploration stage (ngawacak), the conception stage (ngaplan), the execution stage (ngawangun), and the evaluation/ngebah stage (maedeng). The results of the creation of the Bala Ghora Dance are characterized by dynamic movement characteristics but combined with movement elements inspired by sacred rituals. Some of the movement motifs used are the first movement, lifting the left leg with the hand holding the kakereb, which is precisely above the head or crown of the head. Meanwhile, the motif of the second movement is the nengkleng movement by carrying a belocong property or (kecombrang tree trunk). The dance structure consists of eight male dancers. The composition of the Baris Babuang dance creation emphasizes the magical touch of dance, making it unique in strengthening humans' relationship with the universe. Keywords: Baris Babuang, Majabajero, Bala Ghora Dance